2003
DOI: 10.1046/j.1538-7836.2003.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis by antibody blocking the action of proangiogenic high-molecular-weight kininogen

Abstract: Summary. Previously we demonstrated that domain 5 (D5) of high-molecular-weight kininogen (HK) inhibits neovascularization in the chicken chorioallantoic membrane (CAM) assay and further found that kallikrein cleaved HK (HKa) inhibited FGF2-and VEGF-induced neovascularization, and thus was antiangiogenic. In this study, we sought to demonstrate whether uncleaved HK stimulates neovascularization and thus is proangiogenic. The chick chorioallantoic membrane was used as an in ovo assay of angiogenesis. Low-molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…Previous studies (6,10,31) have shown that HKa at nanomolar concentrations inhibits cell proliferation and adhesion and induces apoptosis of endothelial cells in the presence of Zn 2ϩ . Recombinant domain 5 of HKa (GST-D5) partly resembles these effects of HKa, indicating that D5 is likely the active domain responsible for the antiangiogenic activity of HKa.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies (6,10,31) have shown that HKa at nanomolar concentrations inhibits cell proliferation and adhesion and induces apoptosis of endothelial cells in the presence of Zn 2ϩ . Recombinant domain 5 of HKa (GST-D5) partly resembles these effects of HKa, indicating that D5 is likely the active domain responsible for the antiangiogenic activity of HKa.…”
Section: Discussionmentioning
confidence: 95%
“…These findings represent a novel biological function of this molecule. Interestingly, it has recently been demonstrated that bradykinin stimulates angiogenesis (10,21,24). Therefore, HK is a precursor of both an angiogenic stimulator (bradykinin) and an inhibitor (HKa).…”
mentioning
confidence: 99%
“…Intact HK, which under most physiologic circumstances is in molar excess to HKa, is likely to inhibit HKa binding to uPAR under physiological conditions (24 -26). Bradykinin liberated from HK expresses pro-angiogenic activity (26,27). Thus, it is likely that HKa inhibits angiogenesis only in situations where sufficiently large concentrations of these proteolytic fragments have been generated to overcome the competing influence of native plasma HK.…”
Section: Discussionmentioning
confidence: 99%
“…Chick Chorioallantoic Membrane Assay Chick chorioallantoic membrane (CAM) assays were done according to previously published methods (16,17). The surfaces of 10-d-old post-fertilization chick eggs were sterilized and the CAM exposed by cutting a window (1 cm 2 ) on one side of the egg using the false air sac technique.…”
Section: Methodsmentioning
confidence: 99%